Angiotensin-(1-7): A Peptide Hormone with Anti-Cancer Activity - Gallagher, P.E.; Arter, A.L.; Deng, G.; Tallant, E.A. (Current Medicinal Chemistry, 2014)
The development of peptides as therapeutic agents has progressed such that these small molecules of less than fifty amino acids are currently in use for the treatment of a variety of pathologies. This review focuses on the pre-clinical studies and clinical trials assessing the anti-cancer properties of angiotensin-(1-7) [Ang-(1-7)], an endogenous heptapeptide hormone of the renin-angiotensin system. Ang-(1-7) mediates biological responses by activating mas, a unique G protein- coupled receptor, thereby providing specific targeted actions when used as a therapeutic agent. Studies in in vitro as well as in vivo mouse models demonstrated that the heptapeptide hormone reduced proliferation of human cancer cells and xenograft tumors. This attenuation was concomitant with decreased angiogenesis, cancer associated fibrosis, osteoclastogenesis, tumor-induced inflammation and metastasis as well as altered regulation of growth promoting cellular signaling pathways. In three clinical trials, Ang-(1-7) was well tolerated with limited toxic or quality-of-life side effects and showed clinical benefit in cancer patients with solid tumors. Taken together, these studies suggest that Ang-(1-7) may serve as a first-in-class peptide chemotherapeutic agent, reducing cancer growth and metastases by pleiotrophic mechanisms as well as targeting the tumor microenvironment.
Keywords: placental growth factor